Kinship Caregivers: Understanding Children and the Military Deployment Cycle - Elizabeth Thomas; Larry F. Forthun (EDIS)
Deployment occurs in almost every branch of the military, and the experience differs for each family and each family member. To reflect the diversity of experiences, military professionals have proposed various models of the deployment cycle to assist families in the transition. There are at least five phases that are common across models: pre-deployment, deployment, sustainment, preparation (also known as redeployment), and reunification (or home-coming). Recognizing that each family is unique, this deployment cycle is intended not as a rulebook but as a helpful guide to families as they experience deployment of a parent. This 4-page fact sheet was written by Elizabeth Thomas and Larry F. Forthun and published by the UF Department of Family Youth and Community Sciences, March 2013.